Food and Sex-Related Impacts on the Pharmacokinetics of a Single-Dose of Ginsenoside Compound K in Healthy Subjects - Chen, Lulu; Zhou, Luping; Wang, Yaqin; Yang, Guoping; Huang, Jie; Tan, Zhirong; Wang, Yicheng; Zhou, Gan; Liao, Jianwei; Ouyang, Dongsheng (Frontiers in pharmacology, 2017)
Ginsenoside compound K (CK) is a candidate drug for rheumatoid arthritis therapy. This clinical trial was designed to evaluate the effects of food and sex on the pharmacokinetics of CK and its metabolite 20(S)-protopanaxadiol (PPD). An open-label, single-center, two-period crossover trial was performed in healthy Chinese subjects ( = 24; male = 12, female = 12), randomized to either the fasting overnight or the high-fat meal group before a single 200 mg dose of monomer CK was administered. According to the concentration-time data of plasma and urine samples from each subject, the pharmacokinetic parameters of CK and 20(S)-PPD were calculated and statistically analyzed. A two-way ANOVA test combined with mean plots showed no statistically significant interaction between food and sex. High-fat meal accelerated the absorption of CK, with being shortened from 3.6 to 2.5 h ( = 0.015). In contrast, food significantly increased the C , AUC , and AUC ( < 0.001) with the 90% confidence intervals falling outside of the conventional 0.80-1.25. Females had higher exposure levels of CK than males, but the difference was statistically significant only after a high-fat meal. Of note, CK was rarely excreted in urine. Furthermore, the effects of food and sex were also observed on 20(S)-PPD. High-fat food and sex both had an impact on the disposition of CK , but rather than a significant interaction effect. High-fat food accelerated and increased the absorption of CK, while the exposure of CK was higher in females compared to males. The results indicate that food and sex should be two noteworthy factors in future research on CK.